Edukacja ekologiczna w Drugiej Rzeczypospolitej inspiracją dla praktyki edukacyjnej w XXI wieku - Wolter, Edyta (Biuletyn Historii Wychowania, 2016)
This article explains how environmental awareness was raised among primary school pupils in the Second Polish Republic illustrated with an example of “Nasi Przyjaciele” magazine, published by the Society for Protection and Care of Animals in Krakow. The monthly was recommended by the Ministry of Religious Denominations and Public Enlightment for school use. In the specific sections of the magazine, environmental attitudes were promoted by means of articles, appeals to provide environmental education, environmental protection and, last but not least, children’s practical activities as part of the Young Friends of Animals Circle, contests for pupils of elementary schools and their creative co-participation in editing the magazine (stories and poems written by the children were published as the winning contest works). The editors regularly provided answers to children’s questions about care of animals and environmental protection.